Sistem Monitoring dan Kontrol Aeroponik Menuju Smart Greenbox untuk Tanaman Selada berbasis IoT - Karna, Nyoman; Naufal, Rangga; Raniprima, Sevierda; Putra, I Kadek Andrean Pramana; Rahyuni, Dewa Ayu Putu; Parti, I Ketut (Building of Informatics, Technology and Science (BITS), 2023)
Horticultural commodities are agriculture that has a lot of demand in the market. Based on this, a planting system with the aeroponic method was made with an IoT-based monitoring and control system so that its growth is maintained. A system with complex planning is needed to simplify human life. Then a remote monitoring and control system was designed with IoT technology in the aeroponic method. The way this tool works is to send sensor data from the Node MCU via the internet to the cloud and the data is stored in real-time in the Firebase, the data is sent to the Android platform so that the data can be read by the user and the data is sent to a Google spreadsheet automatically which will later be analyzed. Will update data every 15 minutes. In this study, calibration of the DHT11 sensor with HTC Digital obtained an accuracy of 95.5% humidity and 97% temperature, the LDR sensor with LUX meter obtained an accuracy rate of 75.163%, pH sensor with pH meter 97.33%, ultrasonic sensor and ruler. get 100% accuracy, the bandwidth used is 20 Mbps. The network quality test is delayed, with 3 different test times, busy hours (19.00 - 23.00 WIB), empty hours (01.00 - 03.00 WIB), normal hours (12.00 - 14.00 WIB). From network testing, the minimum delay is 0.255 seconds, and the maximum is 0.291 seconds. The results of testing tools during seeding, lettuce plants can grow well.